Seasonal genetic partitioning in the neotropical malaria vector Anopheles darlingi (Diptera: Culicidae) - Angêlla, A.; salgueiro, P.; Gil, L.; Vicente, JL; PintoJ; Ribolla, P. (Malaria Journal, 2014)
Background Anopheles darlingi is the main malaria mosquito vector in the Amazonia region. In spite of being considered a riverine, forest-dwelling species, this mosquito is becoming more abundant in peri-urban areas, increasing malaria risk. This has been associated with human-driven environmental changes such as deforestation. Methods Microsatellites were used to characterize A. darlingi from seven localities along the Madeira River, Rondônia (Brazil), collected in the early and late periods of the rainy season. Results Two genetically distinct subpopulations were detected: one (subpopulation A) was associated with the late rainfall period and seems to be ecologically closer to the typical forest A. darlingi; the other (subpopulation B) was associated with the early rainfall period and is probably more adapted to drier conditions by exploiting permanent anthropogenic breeding sites. Results suggest also a pattern of asymmetric introgression, with more subpopulation A alleles introgressed into subpopulation B. Both subpopulations (and admixed mosquitoes) presented similar malaria infection rates, highlighting the potential for perennial malaria transmission in the region. Conclusions The co-occurrence of two genetically distinct subpopulations of A. darlingi adapted to different periods of rainfall may promote a more perennial transmission of malaria throughout the year. These findings, in a context of strong environmental impact due to deforestation and dam construction, have serious implications for malaria epidemiology and control in the Amazonian region.